Studi Efektivitas Stick Repellent Diperkaya Ekstrak Curcuma longa Dalam Mencegah Gigitan Nyamuk Aedes aegypti - Harijanto, Cyrena Theophania; Pribadi, Florence; Yuwono, Natalia (SENTRI: Jurnal Riset Ilmiah, 2025)
The Aedes aegypti mosquito is the primary vector for the transmission of dangerous diseases such as Dengue Hemorrhagic Fever (DHF), Zika, and Chikungunya. The use of chemical repellents like DEET often leads to side effects, necessitating the search for safer and more environmentally friendly natural alternatives. This study aims to evaluate the effectiveness of a stick repellent formulation enriched with Curcuma longa extract in preventing Aedes aegypti mosquito bites. In this experimental study, five treatment groups were established: a negative control group, three treatment groups with varying concentrations of Curcuma longa extract (10%, 20%, and 40%), and a positive control group using DEET. The tests were conducted on mice with shaved fur, and the number of mosquito bites was recorded every hour for six hours. The data were analyzed using ANOVA and Tukey's post-hoc tests to identify significant differences between the groups. The results indicated that the stick repellent containing 10% Curcuma longa did not provide protection comparable to the positive control. The 20% and 40% concentrations demonstrated higher effectiveness, matching that of the positive control. However, the 40% concentration did not show a significant increase in effectiveness compared to the 20% concentration, suggesting that increasing the concentration of the active ingredient does not always correlate with increased effectiveness.